The Need for “Complementary Information” in the Medical Computer File - Lahaye, D.; Roosels, D.; Viaene, J. (Methods of Information in Medicine, 1978)
The use by the physician of the possibility to add complementary information (C. I.) to each question of a computer file has been analysed using both »APL« and »batch« systems.The analysis of the frequency of use of C.I. by APL leads to the following conclusions: There exist great differences between several physicians in the interpretation of some questions, the ratio of C. I. utilisation frequency reaching in some cases 2:1. This seems clue to the individual »intuitive« approach in each medical examination. The fact that the C. I. is not always filled in at the same place makes this information worthless for statistical analysis.The analysis of the content of the C. I. using the »batch« system makes it possible to identify the questions for which a better instruction of the physician is needed on one hand, and those for which a correction of the question text is necessary on the other hand. The authors think that the complete exclusion of a C. I. possibility is not practicable.
Keywords: Medical File; Occupational Diseases; Pneumoconiosis; APL